Analisis Kepuasan Konsumen terhadap Kualitas Produk dan Layanan “Kedai Kebab Turki” di Kabupaten Karangasem - Zulmia, Naila; Wiranatha, Agung Suryawan; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
The Aims of this research were to: (1) Find out the quality attributes of products and services that considered important by customer to achieve customer satisfaction at Store Kebab Turki (2) Find out the level of conformity of customer expectations and satisfaction on the quality of products and services at Store Kebab Turki (3) To determine the quality attributes of products and services that need to get priority from Store Kebab Turki based on the level of importance and performance to provide customer satisfaction. The method used to measure the level of customer satisfaction in this study by distributing questionnaires related to the analysis of consumer satisfaction on product and service quality to 90 selected respondents and then calculated using the Importance Performance Analysis (IPA) method and the Customer Satisfaction Index (CSI). The results of the research showed that the attribute with the highest level of conformity on product quality were the hygiene and freshness of beverage ingredients with a suitability level 102.12% and attribute with lowest of conformity level is beverage menu variations with a suitability level 94.72%. The attribute with the highest level of conformity on service quality is the availability of knowledge of employees on the products offered with a suitability level 100.27% and attribute with lowest satisfaction level is the availability of parking area with a suitability level 79.17%. The attributes that must be prioritized on product quality are the texture of the food, level maturity food, and the taste of the beverage. The attributes that must be prioritized for service quality are the quickness of service for ordering food and beverage, friendliness and courtesy of employees in serving consumers, interior design and availability of parking area. The CSI results show that all product and service quality attributes are considered important by customer with the average number of MIS values ??greater than 4.20 and customer satisfaction level 84.2% in the very satisfied category for product quality and 79.6% in the satisfied category for service quality. Keywords : customer satisfaction, product quality, service quality, Importance Performance Analysis, Customer Satisfaction Index.